Efforts to increase agility and speed physical education lessons in playing football using student demonstration methods class v Sd negeri 14 perawang barat - Lativa Erni (Fakultas Sastra Universitas Ekasakti, 2018)
Speed ​​and agility are the basic models in playing soccer and for the player is a successful capital to score, and keep goals conceded. With the ability of speed will facilitate the player in order to bring the ball. The problems to be studied in this research are: (a) How to increase the agility and speed of football basics for students in the implementation of demontration method? (B) How is the influence of demonstration methods on student learning motivation. The aims of this research are (a) to know the increasing of agility and speed of learning achievement of soccer basics to students after the implementation of demonstration method; (b) to know the motivation to learn the basics of football after the implementation of demonstration method. This research uses action research as much as two rounds. Each round consists of two stages: design, activity and observation. Reflection and refisi The target of this research is the Grade V student of SD Negeri 14 Perawang Barat from the data obtained in the form of the result of practice test, observation sheet of teaching and learning activity. From the analysis result, it can be found that the students' learning achievement has improved from cycle I to II that is, cycle I (61.54%), cycle II (89,74%) for psychomotro domain, cycle I (84,62%). Cycle II (100%) for the affective domain The conclusion of this research is that the demonstration method can have a positive effect on students' learning motivation V SD Negeri 14 Perawang Barat as well as the modification model can be used as one of alternative physical education.